The Implementation of Polya’s Strategy with Lumio Media to Enhance Students’ Mathematical Problem-Solving Skills on Junior High School - Hanifa; Hulukati, Evi P.; Isa, Dewi Rahmawaty ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Mathematics is a fundamental discipline that plays an important role in developing students' logical, analytical, and systematic thinking skills. However, many students still struggle with solving non-routine mathematical problems due to a reliance on memorization and teacher-centered learning. This study aims to improve students’ mathematical problem-solving ability, especially in probability, through the implementation of Polya’s problem-solving steps assisted by Lumio interactive media. This classroom action research employed the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages conducted over two cycles. The research subjects were 12 eighth-grade students from SMP Muhammadiyah Kwandang. Data were collected through tests and observation sheets, then analyzed both quantitatively and qualitatively. The instruments included essay tests based on probability story problems and validated observation sheets for teacher and student activities. The results showed a significant improvement in students’ problem-solving skills. The average score increased from 70.05% in the first cycle to 83.59% in the second cycle. The proportion of students achieving mastery also rose from 33% to 91.7%. Learning activities became more interactive and student-centered. It is concluded that integrating Polya’s strategy and Lumio media is effective in enhancing students’ mathematical problem-solving skills and active learning engagement.